Emulsion Electrospun Fiber Mats of PCL/PVA/Chitosan and Eugenol for Wound Dressing Applications - Cláudia Mouro; Manuel Simões; Isabel C. Gouveia (Advances in Polymer Technology)
In recent years, the damaging effects of antimicrobial resistance relating to wound management and infections have driven the ongoing development of composite wound dressing mats containing natural compounds, such as plant extracts and their derivatives. The present research reports the fabrication of novel electrospun Polycaprolactone (PCL)/Polyvinyl Alcohol (PVA)/Chitosan (CS) fiber mats loaded with Eugenol (EUG), an essential oil, known for its therapeutic properties. The electrospun fiber mats were prepared via electrospinning from either water-in-oil (W/O) or oil-in-water (O/W) emulsions and characterized using scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR), total porosity measurements, and water contact angle. The in vitro EUG release profile and antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa were also evaluated. The obtained results proved that the EUG was loaded efficiently into electrospun PCL/PVA/CS fiber mats and the two W/O and O/W emulsions prepared from the PCL/PVA/CS (7 : 3 : 1) and PCL/PVA/CS (3 : 7 : 1) revealed porosity within the ideal range of 60–90%, even when EUG was loaded. The measured contact angle values showed that the O/W emulsion exhibited a more hydrophilic character and the wettability noticeably decreased after adding EUG in both emulsion blends. Furthermore, the electrospun PCL/PVA/CS fiber mats demonstrated a rapid release of EUG during the first 8 hours, which enhanced gradually afterward (up to 120 hours). Moreover, an efficient antibacterial activity against S. aureus (inhibition ratios of 92.43% and 83.08%) and P. aeruginosa (inhibition ratios of 94.68% and 87.85%) was displayed and the in vitro cytotoxic assay demonstrated that the normal human dermal fibroblasts (NHDF) remained viable for at least 7 days, after direct contact with the produced electrospun fiber mats. Therefore, such findings support the biocompatibility and suitability of using these EUG-loaded electrospun PCL/PVA/CS fiber mats as a new innovative wound dressing material with potential for preventing and treating microbial wound infections.